Impact of Sengkubak Leaf Extract and Storage Time on some Physicochemical and Microbial Attributes of Ready-to-Eat Bakso Ayam (Chicken Meatballs) - Amalia, Dian Nur; Kayihura, Joseph F; Khalisanova, Sabrina Zulfa; Arsita, Tiara Ajeng; Rusman, Rusman; Triyananto, Endy (Jurnal Teknologi Hasil Peternakan, 2025)
Bakso ayam are chicken meatballs produced using natural additives, and have been found to possess a higher level of safety for regular dietary intake. Sengkubak (Pycnarrhena cauliflora) is an indigenous plant mostly found in West Kalimantan which is commonly used by local communities as a natural food flavoring. In this study, the effect of dry aqueous sengkubak extract concentration (0% as control; 0.25%; 0.5%; and 0.75%) and storage time (0 week as control, 4 weeks, and 8 weeks) at ~27°C on some physicochemical and microbial quality of bakso ayam was examined. Other variables examined was the sensory attributes and glutamic acid content. The glutamic acid concentration of sengkubak leaf extract was found to be 5.4%.  The data analysis used variance analysis (ANOVA) of a complete random pattern (RAL) by three repetitions Furthermore, level of sengkubak extract affected most physical qualities parameters, glutamic acid content and sensory attributes, but it did not affect protein content. While, storage time affected WHC, all chemical qualities, total microbes, but did not affect sensory attributes. The addition of 0.5% sengkubak leaf extract is recommended in this study because it produced the best firmness (7.82 gf), protein content (11.87%), and taste among all treatments. Bakso ayam was safe for consumption until the 8th week of storage at room temperature (±27°C).